A realist evaluation of local networks designed to achieve more integrated care - Rea, Harry; Cumming, Jacqueline; Pledger, Megan; Middleton, Lesley (International journal of integrated care, 2019)
Introduction: Policies encouraging health services to deliver care “closer to home” have been a consistent theme in forward directions for the New Zealand health sector. Responsibility for deciding how to achieve this broad goal falls individually to 20 District Health Boards. As part of a wider programme of system integration, one District Health Board – Counties Manukau District Health Board - grouped local health providers into 4 geographical localities to create four new networks with responsibility for local planning, design and delivery. Not surprisingly given their multi-component nature,initiatives to improve integrated care often evolve to find the best way to bring about change. This is an example of how an evaluation evolved alongside such an initiative designed to better integrate care across primary, community and hospital services. Theory and methods: Using the explanatory power of a realist evaluative approach, theories concerning the new behaviours that would be adopted were explored in: (i) interviews with stakeholders in 2012 and 2015, (ii) a purposive sample of ten general practices, and (iii) online surveys of general practices and local care organisations.  Results: In an environment where the central narrative of what the Localities initiative was expected to do shifted from a focus on a risk/gain share contract to local networks acting as “an incubator of integration”, providers made sense of the changes by testing whether they improved their knowledge around who to contact to arrange care for individual patients. Discussion: Building an understanding of the behavioural landscape of professionals offered value despite the major shifts in what was happening to drive change. Conclusion: Given the multi-component and evolving nature of initiatives seeking to better integrate care, the realist evaluative emphasis on surfacing early the theories to explain how change is expected to occur, helps overcome the challenge of evaluating “a moving target”. Lessons learned: Temper the expectation that the creation of four localities would reduce demand for secondary care and be more targeted about which local relationships need to be improved in order to benefit which groups of patients. Limitations: The experience confirms the challenges of the field of integrated care, which can easily be saddled with ambitious business cases claiming significant effects when the reality is that behavioural changes are much more nuanced. Suggestions for future research: The strength of this evaluation centres on the application of the realist approach. Recognising that the Localities initiative is a social programme involving human decisions and actions, attention was paid to identifying how change is expected to occur, and then testing the extent to which these theories were borne out.